A pooled analysis of 2 placebo-controlled 18-month trials of lamotrigine and lithium maintenance in bipolar I disorder. - Goodwin, G; Bowden, C; Calabrese, JR; Grunze, H; Kasper, S; White, R; Greene, P; Leadbetter, R (2004)
BACKGROUND: Two clinical trials, prospectively designed for combined analysis, compared placebo, lithium, and lamotrigine for treatment of bipolar I disorder in recently depressed or manic patients. METHOD: 1315 bipolar I patients (DSM-IV) enrolled in the initial open-label phase, and 638 were stabilized and randomly assigned to 18 months of double-blind monotherapy with lamotrigine (N = 280; 50-400 mg/day fixed dose or 100-400 mg/day flexible dose), lithium (N = 167; serum level of 0.8-1.1 mEq/L), or placebo (N = 191). The primary endpoint was time from randomization to intervention for a mood episode. Data were gathered from August 1997 to August 2001. RESULTS: Lamotrigine and lithium were superior to placebo for time to intervention for any mood episode (median survival: placebo, 86 days [95% CI = 58 to 121]; lithium, 184 days [95% CI = 119 to not calculable]; lamotrigine, 197 days [95% CI = 144 to 388]). Lamotrigine was superior to placebo for time to intervention for depression (median survival: placebo, 270 days [95% CI = 138 to not calculable]; lithium, median not calculable; lamotrigine, median not calculable). Lithium and lamotrigine were superior to placebo for time to intervention for mania (median survival not calculable for any group). Results of additional analyses adjusted for index mood were similar; however, only lithium was superior to placebo for intervention for mania. There was no evidence that either active treatment caused affective switch. Adverse event analysis indicated more diarrhea (19% vs. 7%, p <.05) and tremor (15% vs. 4%, p <.05) in lithium-treated patients compared with lamotrigine-treated patients. CONCLUSIONS: Lamotrigine and lithium stabilized mood by delaying the time to treatment for a mood episode. Lamotrigine was effective against depression and mania, with more robust activity against depression. Lithium was effective against mania.